Challenges and opportunities in applying genomic selection to ruminants owned by smallholder farmers - Burrow, H.M.; Mrode, Raphael A.; Okeyo Mwai, Ally; Coffey, M.P.; Hayes, B.J. (MDPI, 2021)
Genomic selection has transformed animal and plant breeding in advanced economies globally, resulting in economic, social and environmental benefits worth billions of dollars annually. Although genomic selection offers great potential in low- to middle-income countries because detailed pedigrees are not required to estimate breeding values with useful accuracy, the difficulty of effective phenotype recording, complex funding arrangements for a limited number of essential reference populations in only a handful of countries, questions around the sustainability of those livestock- resource populations, lack of on-farm, laboratory and computing infrastructure and lack of human capacity remain barriers to implementation. This paper examines those challenges and explores opportunities to mitigate or reduce the problems, with the aim of enabling smallholder livestock- keepers and their associated value chains in low- to middle-income countries to also benefit directly from genomic selection.